The Use of Snowball Throwing in Teaching Reading at The Second Year Students of SMPN 8 Palopo - Wahidin, Wahidin (FOSTER: Journal of English Language Teaching, 2020)
This thesis uses snowball to improve student reading with the research question, "How to use snowball throwing in SMPN's second-year students. This research employed Classroom Action Research (CAR) with cycles: first cycle, second cycle. Each cycle consists of four steps: planning. Acting, observing, reflecting. Four meetings during the research cycle. Class VIII, three samples of this study, consisted of 20 students. The study result revealed that Cycle 2 was better than Cycle one scores. During the lesson, the students showed great enthusiasm. Cycle 2's mean score is 82,75, and the percentage of student activity observation The student reading mastery increases after Cycle 2. The appropriate way to teach reading using snowball throwing is: (1) giving students more motivation to build confidence and spirit to study hard and be active in learning. (2) Before starting the learning process, more explanation of the material and giving the game than allowing the students to say what they do not understand. (3) Giving reward/gift for appreciation, (4) grouping students into a small group of 5 students. (5) Narrative text glossaries (6) Observers and writers were observing student activities. (7) Testing students to know the students ' improvement in reading after Using Snowball Throwing Learning (focus on the narrative text)